PTH-037 Adherence To 2013 Bsg Barrett's Oesophagus Surveillance Guidelines Could Facilitate Safe Discharge Of Patients. (9th June 2014) - Walker, G; Moini, N; Mayall, F; Pugh, S
Abstract : Introduction: The prevalence of Barrett's oesophagus (BO) is increasing and surveillance of this population is a growing burden for endoscopy units. 1 Guidelines exist to facilitate quality surveillance but are poorly adhered to. 2 We evaluated previous endoscopy (OGD) and histology reports of patients due to undergo BO surveillance in 2014 at a UK district general hospital. By using the 2013 BSG guidelines we decided if sufficient data were available to discharge patients or increase their surveillance interval. 3 Methods: The endoscopy department provided a list of all adult patients booked for BO surveillance in 2014. Electronic reports were used to find the length of BO, presence/absence of intestinal metaplasia (IM), adherence to the Prague CandM criteria and compliance with the Seattle biopsy protocol (4 biopsies every 2 cm). A Consultant pathologist clarified any uncertain histology reports. Outcomes after reviewing the cases were: 'discharged from surveillance', 'delayed OGD' or 'no change to date of OGD'. No patients with long segment BO(>3 cm) had their endoscopies delayed. Finally hypothetical outcomes were calculated assuming all previous OGD's were compliant with BSG standards. Data were entered into an Excel spreadsheet and simple statistics used to analyse findings. Results: 125 patients were due BO surveillance in 2014. 96 male (77%), average age 64 years (range 34–84). 76 (61%) endoscopy reports were compliant with Prague CandM criteria. 33 (26%) reports were compliant with the Seattle biopsy protocol, whilst 92 (74%) were not. In 110 (88%) cases no change was made to the planned surveillance date, either due to inadequate biopsies being taken to delay/discharge or appropriate date of surveillance already booked. 15/125 (12%) patients were either discharged or had their OGD delayed. If all procedures had been compliant with BSG standards this might have led to more than three times as many patients having their surveillance discontinued or delayed (48/125:38%). Conclusion: Using the 2013 BSG guidelines enables departments to safely discharge patients with Barrett's oesophagus or increase surveillance intervals. This will save money and reduce the risk and discomfort inherent with this program. Endoscopists adherence to the Seattle biopsy protocol is poor, and this is the main barrier preventing more patients from being discharged. References: 1 Coleman HG, et al . Increasing incidence of Barrett's oesophagus: a population-based study. Eur J Epidemiol 2011;26(9):739–45 2 Abrams JA, et al . Adherence to biopsy guidelines for Barrett's esophagus surveillance in community setting in the USA. Clin Gastroenterol Hepatol 2009;7(7):736–42 3 Fitzgerald RC, et al . British Society of Gastroenterology guidelines on the diagnosis and management of Barrett's oesophagus. Gut 2014;63:7-42 Disclosure of Interest: None Declared.